A Study on Linear Shrinkage Behavior of Peat Soil Stabilized with Eco-Processed Pozzolan (EPP) - Mohamad S. Sulaiman; Habib M. Mohamad; Anis A. Suhaimi (Civil Engineering Journal, 2022)
Peat soil incorporated materials from fragmented organic constituents that originated in submerged wetlands. Peat soil has a particular index property that accounts for more than 75% of its organic content. Due to its low shear strength, high moisture content, high compressibility, low specific gravity, restricted bearing capacity, irregular shrinkage, and instability, peat soil is interpreted as a challenging soil for the building industry. The purpose of this study is to look at the index properties of Klias, Beaufort peat soil, and eco processed pozzolan (EPP), as well as to investigate the strengthening and stiffening effects of EPP stabilization treatment on peat soil and the association between EPP and linear shrinkage effects of peat. The linear shrinkage used to measure the shrinkage behaviour of peat soil consists of untreated samples, namely peat soil, and treated samples, which are peat soil in addition to EPP with a concentration of 20% and 30%, respectively. A scanning electron microscope (SEM) is employed to produce images of a sample by scanning the surface of an untreated peat sample and treated peat samples with EPP. High moisture content with an average of 580% was reported for the KBpt area. EPP can potentially help to reduce the shrinkage by almost 66.66%. Additionally, the results showed that by adding EPP as filler material to the peat soil, shrinkage behaviour decreases significantly for untreated peat soil and treated peat soil with EPP, with 4.29% reduced to 1.43% significantly. Correspondingly, the crystallization process occurred between peat soil and EPP, which contributed to the reduction of shrinkage and tension crack in peat soil and produced Muscovite, which is appeared and identified as mineral that important in rock-forming mineral. Doi: 10.28991/CEJ-2022-08-06-05 Full Text: PDF